Pengaruh Perencanaan Pajak Dan Beban Pajak Tangguhan Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Industri Yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2024) - Fira Asnifa Rahmadanti; Mahwiyah Mahwiyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of tax planning and deferred tax expense on earnings management in manufacturing companies in the industrial subsector listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Earnings management can be implemented through various methods, one of which is utilizing tax planning strategies and recognizing deferred tax expense. This study uses a quantitative approach with secondary data obtained from company financial reports. The sample size for this study was 35 companies, selected using a purposive sampling method. The results indicate that: a) tax planning variables have a significant effect on earnings management with a significant value; deferred tax expense does not have a significant effect on earnings management with a significant value; c) simultaneously, tax planning and deferred tax expense have a significant effect on earnings management. These findings suggest that companies need to consider optimal tax planning strategies to support efficient and ethical financial reporting.